A STUDY OF LINGUISTIC FEATURES OF THE NAMES OF COFFEE SHOPS IN ENGLISH VERSUS VIETNAMESE - HUỲNH THỊ THANH TRANG (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is aimed: - To help learners of English as a foreign language understand the structural features of the names of coffee shops in English versus Vietnamese. - To help learners of English as a foreign language understand the semantic features of coffee shops in English versus Vietnamese. - To give the cross cultural communicators and learners of English and Vietnamese as a foreign language have a good insight into the cultural, historical features of English versus Vietnamese.